Rola prawa międzynarodowego w rozwoju nauki o stosunkach międzynarodowych - Parzymies, Stanisław; Symonides, Janusz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Stosunki międzynarodowe jako samodzielna dyscyplina naukowa zrodziły się z prawa międzynarodowego. W teorii stosunków międzynarodowych słusznie zwracano uwagę, że normy prawne nie są w stanie całkowicie określać postępowania państw, że wpływa na nie wiele innych czynników: siła, interesy, wartości... Jednak krytyka ta idzie zbyt daleko, prowadz¹c do niedoceniania czy wręcz kwestionowania znaczenia prawa międzynarodowego dla stosunków międzynarodowych. Żaden bowiem porządek międzynarodowy nie może istnieć bez norm prawa międzynarodowego. Koniec zimnej wojny stworzył nową jakościowo sytuację dla jego umacniania. Dochodzi do istotnej ewolucji i rozwoju prawa międzynarodowego. Jesteśmy świadkami postępującego upodmiotowienia jednostki. Ewolucji podlega pojęcie suwerenności. Zasada nieinterwencji ustępuje miejsca odpowiedzialności państwa za ochronę jego ludności. Sprawcy zbrodni międzynarodowych w wyniku rozwoju sądownictwa międzynarodowego pociągani są do odpowiedzialności karnej. Kończy się era bezkarności za naruszanie norm prawa międzynarodowego. Pojęcie społeczności i podmiotowość wymaga jednak w XXI wieku redefinicji. Mimo ogromnego wzrostu liczby i znaczenia aktorów niepaństwowych w stosunkach międzynarodowych, zasadniczym ich elementem pozostają nadal państwa. System Narodów Zjednoczonych powinien być zreformowany. Narody Zjednoczone, organizacje regionalne i integracyjne wymagają niezbędnych inicjatyw, by człowiek i jego potrzeby stanęły w centrum ich działalności. Znaczenie prawa międzynarodowego nie tylko nie maleje, lecz wzrasta.

International relations as an independent new discipline has been created by a process of sep - aration from international law. The theory of international relations very rightly stressed that States’ conduct neither can be fully determined nor can be viewed and analyzed exclusively by a prism of legal norms. Nevertheless, such approach can be criticized when it leads to underesti- mation, neglect or even rejection of any role for international law in international relations. In fact none international order can exist without principles, norms, procedures and institution based and created by international law. The end of the Cold War has created new opportunities for development and evolution of international law. One can observe profound changes concern- ing the notion of sovereignty, subjectivity, responsibility. The principle of non-intervention is re- placed by the UN principle „responsibility to protect”. Individuals responsible for international crimes due to the creation of many international tribunals are brought to criminal responsibility. An era of impunity comes to the end. Notion of international community and subjects of interna- tional law needs in 21 st century a redefinition. Despite great increase of numbers and importance of non-state actors States preserve their dominant position. United Nations system should be re - formed. All intergovernmental, international organizations should put human beings of the cen - ter of their activities. The role and importance of international law in 21 st century is on rise. This is due to the need to meet new challenges and threats confronting international community. That why, international agreements and regulations are indispensible. International law is also under influence of new processes in particular globalization, regionalization and integration, including the European Union. Studies of international relations cannot be properly developed and brought adequate and just results without taking into account international law. By the same token inter - national law without taking into account broadly understood international relations is threaten to be dogmatic and disconnected from reality.
International Law and the Development of International Relations